2016
DOI: 10.5604/01.3001.0009.5273
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and sedative effects of perioperative gabapentin in total knee arthroplasty: a randomized, double-blind, placebocontrolled dose-finding study

Abstract: Gabapentin has shown acute postoperative analgesic effects, but the optimal dose and procedure-specific benefits vs harm have not been clarified. In this randomized, double-blind, placebo-controlled dose-finding study, 300 opioid-naive patients scheduled for total knee arthroplasty were randomized (1:1:1) to either gabapentin 1300 mg/d (group A), gabapentin 900 mg/d (group B), or placebo (group C) daily from 2 hours preoperatively to postoperative day 6 in addition to a standardized multimodal analgesic regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 0 publications
0
48
0
Order By: Relevance
“…However, gabapentinoids can cause sedation and dizziness and both these symptoms are undesirable for enhanced recovery. Some studies have failed to show analgesic benefit …”
Section: Gabapentinoidsmentioning
confidence: 99%
“…However, gabapentinoids can cause sedation and dizziness and both these symptoms are undesirable for enhanced recovery. Some studies have failed to show analgesic benefit …”
Section: Gabapentinoidsmentioning
confidence: 99%
“…Gabapentin has been used to treat postoperative acute and chronic pain following major lower limb surgery [7,[18][19][20][21]. However, a recent well-designed study found that the use of gabapentin cannot prevent acute postoperative pain following TKA, and it resulted in increased adverse reactions [12].…”
Section: Discussionmentioning
confidence: 99%
“…Gabapentinoid drugs have relatively mild side effects, but high doses can cause dizziness, sedation, nausea, loss of balance, lower limb edema, urinary retention, constipation, and pruritus [11,12,30]. Several studies using gabapentinoids for acute postsurgical pain have reported PONV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The "gabapentinoids section" gives no relevant information based on the many well-designed and even dose-finding studies of these drugs, mostly being negative. [5][6][7] Also, the review lacks focus on the potential adverse effects of these drugs. Furthermore, there is no mention of the potential for highdose preoperative steroids, with several positive randomized controlled trials.…”
Section: Anesthesia and Analgesia For Total Knee Arthroplastymentioning
confidence: 99%